DEMOGRAPHIC CHARACTERISTICS OF THE SEROPREVALENCE OF HUMAN TOXOCARIASIS AMONG THE POPULATION OF NORTH-EASTERN BULGARIA - Tatyana Cvetkova; Kalina Stoyanova; Tsonko Paunov; Stoyan Pavlov (Peytchinski Publishing, 2021)
Toxocariasis is a tissue zoonosis caused by Toxocara spp. and the exposure to these geohelminths varies in different parts of the population in a particular region. The purpose of the study is to reveal the seroprevalence of toxocariasis in North-eastern Bulgaria and to establish its demographic structure. Material/Methods: Within the scope of a broad seroepidemiological study, 701 individuals from North-eastern Bulgaria were tested for anti-Toxocara antibodies (ELISA) between 2017 and 2020. The results were stratified and analysed by age, gender, and place of residence. Results: The overall seroprevalence of human toxocariasis in North-eastern Bulgaria is 18.54%. Children (18.85%) and adults (18.30%) show similar levels of infection, but the stratified analysis by age in 5-years intervals revealed notable discrepancies. In younger children, the seroprevalence is higher than the observed for the entire population (0-4 years - 22.22%; 5-9 years - 22.22%), while in adolescents and adults is lower than average. In the elderly, the seroprevalence rises to its highest levels (60-64 years - 30.56% and over 65 years -31.67%). Although there are variations between males and females, gender is not a significant factor for the distribution of toxocariasis. Higher seroprevalence levels in residents of the smaller settlements of the region (children - 28.18%; adults -29.10%) correspond to a 2.5-fold increase in the odds of contracting toxocariasis in comparison to the ones living in Varna city. Conclusion: The overall seroprevalence of toxocariasis in North-eastern Bulgaria is alarmingly higher than the levels reported from other parts of the country, placing this unknown infection in a leading position among the parasitic zoonoses. The place of residence is the most significant factor driving the uneven distribution of the disease.